2015
DOI: 10.1016/j.neuron.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Inputs to Intercalated Cells Provide Fear-Learning Modulated Inhibition to the Basolateral Amygdala

Abstract: Increasing evidence suggests that parallel plastic processes in the amygdala involve inhibitory elements to control fear and extinction memory. GABAergic medial paracapsular intercalated cells (mpITCs) are thought to relay activity from basolateral nucleus (BLA) and prefrontal cortex to inhibit central amygdala output during suppression of fear. Recently, projection diversity and differential behavioral activation of mpITCs in distinct fear states suggest additional functions. Here, we show that mpITCs receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 63 publications
12
94
0
1
Order By: Relevance
“…Although foot shock-induced Fos activation in the sensory thalamus has not been described, electrophysiological measurements showed that foot shock and pinch do activates the sensory thalamic neurons (e.g. posterior intralaminar thalamic nuclei, PIN) (Asede et al, 2015; Bienvenu et al, 2015), as well as the PBel neurons (Bernard and Besson, 1990; Bester et al, 2000), and the PIN sends excitatory projections to both intercalated neurons and principal neurons in the LA (Asede et al, 2015; Bienvenu et al, 2015). Thus, the spino-thalamic and spino-parabrachial circuits may coordinately activate the CeA and LA to establish robust learning about threats.…”
Section: Discussionmentioning
confidence: 99%
“…Although foot shock-induced Fos activation in the sensory thalamus has not been described, electrophysiological measurements showed that foot shock and pinch do activates the sensory thalamic neurons (e.g. posterior intralaminar thalamic nuclei, PIN) (Asede et al, 2015; Bienvenu et al, 2015), as well as the PBel neurons (Bernard and Besson, 1990; Bester et al, 2000), and the PIN sends excitatory projections to both intercalated neurons and principal neurons in the LA (Asede et al, 2015; Bienvenu et al, 2015). Thus, the spino-thalamic and spino-parabrachial circuits may coordinately activate the CeA and LA to establish robust learning about threats.…”
Section: Discussionmentioning
confidence: 99%
“…The infralimbic cortex (IL) indirectly projects to the CeM via intercalated cells in rats but not in mice Sesack 2000, 2008;Strobel et al 2015). It is thought that the ITC cells mediate extinction (Quirk et al 2003;Likhtik et al 2008) but may play a more general role in gating fear behavior, as they also receive direct sensory inputs (Asede et al 2015;Strobel et al 2015). Moreover, PL and IL receive amygdala projections originating mainly from the basal amygdala.…”
Section: Neural Circuitrymentioning
confidence: 99%
“…Yet, how nociceptive signals are detected by the BLA learning system is still unclear. Some studies suggest that the sensory discriminative component of the nociceptive information is conveyed to the BLA via a spino-thalamic tract composed of lamina I spinal cord neurons targeting the posterior intralaminar thalamic nucleus (PIN), which in turn sends excitatory projections to the BLA (Asede et al 2015;Bienvenu et al 2015). However, this hypothesis has been challenged by studies showing that fiber-sparing lesions in this area do not impair footshock learning (Brunzell and Kim 2001;Lanuza et al 2008;Herry and Johansen 2014).…”
Section: Noxious Stimulimentioning
confidence: 99%